Desenvolvimento de união de multimateriais através de rebitagem por injeção (Injection Clinching Joining) - Abibe, André Bastos (Universidade Federal de São Carlos, 2011)
Multimaterial structures are currently a technologically attractive field of research. The growing use of polymer composites replacing metals in structures aiming for weight and emission reduction is part of the motivation of this study. The currently used techniques adhesive bonding and mechanical fastening are limited in certain aspects, opening a path for innovation in this area. Joining of polymers and metals via Injection Clinching Joining (ICJ) is an innovative technique based in injection molding, adhesive bonding and staking. This work studies this technology in its theoretical aspects and applies it to a preliminary study with commercial materials: 30% short glass fiber reinforced polyamide 6,6 (PA66/FG30%); and aluminum alloy AA2024-T351. A design of experiment of one factor at a time analyzed effects of the process parameters on macro- and microstructure, local and global mechanical properties, and thermal properties. It was possible to create joints in which the polymer completely filled cavities in the metallic hole, but the reproducibility was not good, for most joints had only partial filling of the cavities, factor which improves the mechanical performance of the joint. The lap shear testing of overlapped joints determined the global mechanical strength of the joint, which ranged from 20,90 MPa to 51,48 MPa (35,9% to 88,5% of the ultimate tensile strength of PA66/FG30%), and the best performances are attributed to a large contact volume of polymeric material with the chamfer on top of the stud, and effective cavity filling. Two types of fracture were observed, a ductile and gradual (rivet pull-out), and a fragile and catastrophic (net-tension). The thermal properties of the polymer after joining were not significantly changed compared to the base material. This scientific and technological research featured ICJ as a viable process for joining of multimaterial structures, achieving good mechanical performance without significantly changing the properties of the base materials.
Development of multimaterial joints through injection clinching joining
Keywords: Plásticos; Termoplásticos; Poliamida 6.6; Estruturas híbridas; Alumínio; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA